Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1167/iovs.12-10408
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Endothelial Growth Factor Receptor 1 Morpholino Increases Graft Survival in a Murine Penetrating Keratoplasty Model

Abstract: VEGFR1_MO decreased angiogenesis and lymphangiogenesis, resulting in increased graft survival in both NR PK and HR PK. This beneficial effect is synergistically enhanced with steroid treatment in HR PK.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 41 publications
0
24
0
2
Order By: Relevance
“…Lately, there have also been novel approaches to immunomodulate alloimmunity that have focused on morpholine oligonucleoitides, 32 cell-specific gene therapy, 34 RNA interference, 146 and anti-VEGF therapy, 162 with promising experimental results.…”
Section: Novel Strategies For Immunomodulation In Corneal Transplamentioning
confidence: 99%
“…Lately, there have also been novel approaches to immunomodulate alloimmunity that have focused on morpholine oligonucleoitides, 32 cell-specific gene therapy, 34 RNA interference, 146 and anti-VEGF therapy, 162 with promising experimental results.…”
Section: Novel Strategies For Immunomodulation In Corneal Transplamentioning
confidence: 99%
“…43 A new recombinant fusion protein, named aflibercept [or VEGF-Trap (R1R2) ], has also been developed recently for antiangiogenic therapy. Aflibercept recombinant fusion protein has two main components; the VEGF-binding portions from the extracellular domains of human VEGF receptors 1 and 2 are further fused to the Fc portion of human immunoglobulin 1 to form the antibody.…”
Section: Soluble or Modified Vegf Receptorsmentioning
confidence: 99%
“…Cho et al reported that combining steroid treatment with VEGFR-1 morpholino, a synthetically produced molecule that binds mRNA to inhibit translation or alternative splicing, decreases both angiogenesis and lymphangiogenesis and improves corneal graft survival in a high-risk corneal transplantation murine model. 194 In addition, a combination of Flt23k nanoparticles that deliver plasmids expressing anti-VEGF intrareceptor Flt23k and steroid treatment significantly reduces lymphangiogenesis and improves graft survival in a mouse model of corneal transplantation. 195 …”
Section: Diseases Associated With Corneal Lymphangiogenesismentioning
confidence: 99%